Lewis Blood-group Antigens Are Associated With Altered Susceptibility to Shigellosis. (17th September 2020) - Leslie, Jhansi L; Weddle, Erin; Yum, Lauren K; Lin, Ye; Jenior, Matthew L; Lee, Benjamin; Ma, Jennie Z; Kirkpatrick, Beth D; Nayak, Uma; Platts-Mills, James A; Agaisse, Herve F; Haque, Rashidul; et al.
Abstract: In a cohort of infants, we found that lack of the Lewis histo-blood group antigen was associated with increased susceptibility to shigellosis. Broadly inhibiting fucosylation in epithelial cells in vitro decreased invasion by Shigella flexneri. These results support a role for fucosylated glycans in susceptibility to shigellosis.